Recent origin of most of the forest cover in the Gabon coastal area - Delegue, M.A.; Fuhr, M.; Schwartz, A.M.; Nasi, Robert (2001)
Variations in the natural 13C abundance of soil organic matter (SOM) at different depths combined with SOM radiocarbon dating were used to reconstruct the history of the forest-savanna successions over the last millennium in the Gabon coastal area. A chronosequence was established by comparing the '13C profiles and the radiocarbon dating of a Gabon savanna with those of a Congolese savanna where the palaeoenvironments are already well known. The palaeoclimatic histories of the two savannas were shown to be strictly identical. The whole Gabon coastal area may well have been forested during the early Holocene, until about 4,000 years ago. The forest fragmented after this initial expansion. Savanna appeared circa 3,000 years ago but the forest did not disappear totally. A new forest transgression started 500-1,000 years ago and expanded over the open areas previously created or enlarged. The marked savanisation and the subsequent and currently ongoing forest expansion explain both the present forest-savanna mosaic and the abundance of secondary species such as Aucoumea klaineana in the coastal forest. Anthropogenic activities over the past decades and centuries have induced local fluctuations in the forest cover, superimposed on the climatic forest-savanna dynamic. This study also confirms that the monospecific, even-aged A. klaineana stands present in the area became established on abandoned cultivation clearings.